Asymmetric traumatic bilateral dislocation of hip. Case report - Pedro Gonzalo González González; Tamara Elizabeth Morales Perez (Medisur)
A male (26 years) suffered an asymmetric bilateral dislocation of hip as a result of a car accident. The patient was treated with closed reduction and bone traction for six weeks. We present this report since the reviewed literature only include six cases with this kind of lesion and because this is a medical emergency resulting from high impact trauma, being the aseptic osteonecrosis the most significant and serious complication.